Intra-Generational Wealth Distributional Effects on Global Warming Cosat Benefit Analysis - Muir, E. (Journal of Income Distribution®, 1997)
Howarth and Norgaard (1992) showed in the framework of an inter-temporal general equilibrium model, that in the outcome of CBA with regard to global warming is highly dependant on the distribution of rights between present and future generations. They showed that when more rights were awarded to future generations that the ‘efficient’ level of global warming mitigation was much higher than when present generations were awarded a greater share of the rights. This paper extends their work by showing formally that when preferences of consumers within each generation are not identical that the ‘efficient’ outcome of global warming CBA will also be a function of the distribution of intra-generational rights. This reinforces Howarth and Norgaard’s conclusion that it is questions of rights and ethics rather than aggregates of ‘costs and benefits’ that should be paramount in discussion of the appropriate level of global warming mitigation.